Effect of Anti-TNF Therapy on Mucosal Apoptosis Genes Expression in Crohn's Disease - Lykowska-Szuber, Liliana; Walczak, Michal; Skrzypczak-Zielinska, Marzena; Suszynska-Zajczyk, Joanna; Stawczyk-Eder, Kamila; Waszak, Katarzyna; Eder, Piotr; Wozniak, Anna; Krela-Kazmierczak, Iwona; Slomski, Ryszard; Dobrowolska, Agnieszka (Frontiers in Immunology, 2021)
Crohn’s disease (CD) is a chronic immune-mediated disorder for which there is not a fully effective treatment. Moreover, biological therapy with anti-tumor necrosis factor-α (anti-TNF-α) monoclonal antibodies leads to an effective response in only 60–70% of patients. Our previous data suggested that specific loci polymorphism of the TNFRSF1B, FCGR3A, IL1R, IL1B, and FAS genes could be a predictor of the primary non-response to anti-TNF therapy in CD patients. In this work, we propose to explain this hypothesis by functional analysis in colon biopsies and in a cell culture model. Using the RT-qPCR analysis, we estimated the FCGR3A, IL1R, TNFRSF1B, IL1B, FAS, and ADAM17 genes mRNA level in colon biopsies material from inflamed and non-inflamed tissue from 21 CD patients (14 responders and 7 non-responders to anti-TNF therapy) and 6 controls, as well as in vitro in a peripheral blood mononuclear cells (PBMCs) from 14 CD patients (7 responders and 7 non-responders to anti-TNF therapy) and 8 controls cultured for 72 h with 10 µg/ml of anti-TNF antibody. Our findings demonstrated a significant down-regulation of TNFRSF1B gene expression in non-responders both in inflamed and in non-inflamed colon tissue, while the expression of the FCGR3A and IL1B genes was significantly up-regulated in non-responders in the inflamed colon region. In vitro research results indicate that the anti-TNF drug induced a significant decrease in TNFRSF1B, FCGR3A, and FAS gene expression in non-responders. These results show that altered TNFRSF1B, FCGR3A, and IL1B genes expression can be a predictor of the primary non-response to anti-TNF therapy in CD patients.